2006
DOI: 10.1073/pnas.0600625103
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism for diversity in warning signals: Conspicuousness versus toxicity in poison frogs

Abstract: Many animals advertise their chemical defense to predators with conspicuous coloration and unpalatability, but little is known about the information in these signal elements. To effectively avoid predation, is it more advantageous to invest in increased conspicuousness or greater noxiousness, or to allocate equally to both signal modalities? Using natural variation among poison frog species measured with spectral reflectance and toxicity assays, we tested the relative importance of warning signal components wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
193
5
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(205 citation statements)
references
References 32 publications
5
193
5
2
Order By: Relevance
“…Our findings differ from those of Noonan and Honest signaling within aposematic species remains a highly debated topic (Blount et al 2009). For instance, Darst et al (2006) showed signal strength in some members of the poison frog genus Epipedobates (Myers) to be inversely related to their toxicity. Wang (2011) also showed that conspicuous coloration and toxicity were inversely related in Oophaga granulifera (Taylor), a dendrobatid closely related to O. pumilio.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings differ from those of Noonan and Honest signaling within aposematic species remains a highly debated topic (Blount et al 2009). For instance, Darst et al (2006) showed signal strength in some members of the poison frog genus Epipedobates (Myers) to be inversely related to their toxicity. Wang (2011) also showed that conspicuous coloration and toxicity were inversely related in Oophaga granulifera (Taylor), a dendrobatid closely related to O. pumilio.…”
Section: Discussionmentioning
confidence: 99%
“…These cardenolide compounds act as defensive chemicals in butterflies against their predators (Mebs, Zehner, & Schneider, 2000; Petschenka & Agrawal, 2015; Petschenka et al., 2013; Seiber, Lee, & Benson, 1983). Toxicity level has been used as a measure of noxiousness in aposematic studies combining warning signals and toxicity (Arenas et al., 2014; Blount, Speed, Ruxton, & Stephens, 2009; Darst et al., 2006). Birds use bitterness to estimate the level of toxicity (Skelhorn & Rowe, 2010), and cardenolides are bitter in taste (Malcolm, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…This is because such highly conspicuous colors convey a clear signal, as they are very different from concealed, cryptic colorations (Sherratt & Beatty, 2003) and stand out against heterogeneous environment with varying light conditions (Osorio & Vorobyev, 2005). However, contrary to these expectations, there is increasing evidence that aposematic signals are diverse and conspicuousness among aposematic species varies from highly conspicuous to near cryptic (Darst, Cummings, & Cannatella, 2006; Endler & Mappes, 2004; Merilaita & Ruxton, 2007). …”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, second, we used the contrasts to evaluate total egg conspicuousness (E N ). Following Endler and Mielke (2005) and Darst et al (2010), we calculated the Euclidean distance between pairs of contrasts using E N ¼ (DS 2 þ DL 2 ) 0.5 . As both contrasts were expressed relative to the same backgrounds, this produced a vector in 'perceptual space' (Darst et al 2010), with increasing values indicating greater conspicuousness.…”
Section: Visual Modeling Of Egg Colorationmentioning
confidence: 99%